Warriors. Exile from Shadowclan - Jolley, Dan; Barry, James L., 1979-; Hunter, Erin (New York, NY : Harper Alley, 2022)
On the verge of a bitter leaf-bare, ShadowClan stands on the brink of its own destruction. When battle-obsessed Brokenstar banishes Nightpelt and the rest of ShadowClan's elders to the farthest edges of Clan territory, Nightpelt is shocked at his cruelty. But he's determined to ensure he and his fellow exiles survive the coming frost--and live to reclaim a ShadowClan that takes care of its own. Set during the events of Warriors: The Prophecies Begin, this is a stand-alone adventure.
Created by Erin Hunter.
Kirkus Starred, April 2022
3.6
5-8
Keywords: Cats -- Comic books, strips, etc. -- Juvenile fiction; Animals -- Comic books, strips, etc. -- Juvenile fiction; Survival -- Comic books, strips, etc. -- Juvenile fiction; Clans -- Comic books, strips, etc. -- Juvenile fiction; Cats -- Fiction; Animals -- Fiction; Survival -- Fiction; Clans -- Fiction; Adventure and adventurers -- Fiction; Action and adventure comics; Fantasy comics; Animal fiction; Graphic novels